Biosynthesis of xanthan gum by Xanthomonas campestris LRELP-1 using kitchen waste as the sole substrate. (20th October 2016) - Li, Panyu; Li, Ting; Zeng, Yu; Li, Xiang; Jiang, Xiaolong; Wang, Yabo; Xie, Tonghui; Zhang, Yongkui
Highlights: Xanthan gum was successfully produced from kitchen waste as the sole substrate. The maximum pyruvate content and acetyl content were 6.11% and 2.49%, respectively. The conversion rate of reducing sugar was 67.07%. The fermentation process fitted the Logistic and Luedeking-Piret kinetic models. The thermostability of product was similar to commercial xanthan gum. Abstract: Herein, we report the production of xanthan gum by fermentation using kitchen waste as the sole substrate. The kitchen waste was firstly pretreated by a simple hydrolysis method, after which the obtained kitchen waste hydrolysate was diluted with an optimal ratio 1:2. In a 5-L fermentor, the maximum xanthan production, reducing sugar conversion and utilization rates reached 11.73 g/L, 67.07% and 94.82%, respectively. The kinetics of batch fermentation was also investigated. FT-IR and XRD characterizations confirmed the fermentation product as xanthan gum. TGA analyses showed that the thermal stability of the xanthan gum obtained in this study was similar to commercial sample. The molecular weights of xanthan gum were measured to be 0.69–1.37 × 10 6  g/mol. The maximum pyruvate and acetyl contents in xanthan gum were 6.11% and 2.49%, respectively. This study provides a cost-effective solution for the reusing of kitchen waste and a possible low-cost approach for xanthan production.